Lymphangioma in nasal tip and vestibulum: Case report - Nurinsani Akhmad, Cita; Fadjar Perkasa, Muhammad; Pratiwi Rahardjo, Sutji (Gaceta Médica de Caracas, 2024)
A ‘Pinocchio’ or ‘Cyrano’ nose is a condition with a deformity at the tip of the nose caused by an underlying soft tissue tumor. The deformity of the nose with secondary involvement in the form of lymphangioma is a sporadic case, and few studies have reported it. Lymphangioma itself is a benign tumor that originates from the lymph vessels. The diagnosis of lymphangiomas can be made based on the clinical picture and computed tomography (CT) or magnetic resonance imaging (MRI) scans. Treatment options for nasal tip lymphangioma and nasal vestibule are radiotherapy, cryotherapy, and sclerosant injection.